Marilyn's Beauty Hair Studio / Norfazlina Muhammad ... [et al.] - Muhammad, Norfazlina; Abu Bakar, Siti Hajar; Aris, Siti Aisah; Yusof, Siti Noorain (Faculty of Office Management & Technology, 2004)
Marilyn's Beauty Hair Studio is a unique Beauty Studio located in Plaza Alam Sentral, Shah Alam. Our Beauty Studio offers a wide variety of hair treatments. We have experienced stylist that are dedicated to providing our customers with best ser vices available at the best price. Our care services include haircut, styles, coloring, perm, braids and extensions. Our corrective color and highlighting techniques. Color is a very complex issue and very few stylists do it well. It is generally no a good idea to try and remedy color problems yourself. The results can be traumatic, expensive and take years to correct. For this reason we are here to help you achieve whatever color you desire.